SINTESIS SENYAWA orto-FENILAZO-2-NAFTOL SEBAGAI INDIKATOR DALAM TITRASI - I W. Suirta (Jurnal Kimia (Journal of Chemistry), 2010)
Synthesis of o-fenilazo-2-naphtol used as indicator in titration has been conducted in this research. Thesynthesis was carried out by coupling of diazonium chloride salt with 2-naphtol, and aniline. The product wascharacterized using spectroscopy techniques (IR, 1HNMR, and MS), while the pKHIn was determined using UV-visspectrometer. The application of the product as indicator in titration was compared to methyl-orange.The synthesis gave a red crystal with 62.51 % yield. Infra red spectra analysis showed the presence ofcharacteristic functional groups such as–OH, CH-aromatic, C=C, N=N, CN, CO, and a peak indicated substituents atortho position. 1HNMR showed three separated peaks. Mass spectra gave molecular ion peak (M+) at m/z 248. Thered crystal obtained melted at 128-131oC. Based on spectroscopy analysis and melting point, it can be concludedthat the product was o-fenilazo-2-naphtol. The product had a pKHin of 3.16, therefore it can be used as indicator foracid-base titration which showed equivalent point at pH 5.